2016
DOI: 10.1007/s00417-016-3385-z
|View full text |Cite
|
Sign up to set email alerts
|

Outer retinal deformity detected by optical coherence tomography in eyes with foveal hypoplasia

Abstract: In eyes with foveal hypoplasia with severe structural immaturity, diffuse HFL or no HFL was associated with worse vision. There was greater foveal immaturity in eyes with foveal hypoplasia with aniridia compared with foveal hypoplasia as an isolated entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…[44] Katagiri et al . [45] reported that different OCT images of Henle's fiber layer reflected different grades of foveal maturity with regard to the visual acuity in eyes with aniridia and isolated foveal hypoplasia.…”
Section: Diseases Known To Be Associated With Foveal Hypoplasia Beformentioning
confidence: 99%
“…[44] Katagiri et al . [45] reported that different OCT images of Henle's fiber layer reflected different grades of foveal maturity with regard to the visual acuity in eyes with aniridia and isolated foveal hypoplasia.…”
Section: Diseases Known To Be Associated With Foveal Hypoplasia Beformentioning
confidence: 99%
“…The patient demographics were analyzed using the two-tailed and non-paired t -tests for the age at examination or chi-square test for gender. Each measurement parameter between eyes with ONH and controls was analyzed using the mixed effect model for repeated measurements following the previous study 29 . The other parameters included the GCC thickness and that from the INL to the RPE in each macular region, optic disc area, RNFL thickness and that from the INL to the RPE in each circumpapillary region, and each component of the FF-ERG and FM-ERG amplitudes and implicit times.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Foveal hypoplasia (FH) refers to underdevelopment of the fovea, characterized by the continuity of inner retinal layers in the presumed foveal area; the foveal avascular zone may be limited or absent, and retinal vessels may be seen coursing through the foveal region. 1,2 It is commonly associated with ocular conditions such as aniridia, albinism, achromatopsia, or a PAX6 mutation. 3 Less commonly, isolated foveal hypoplasia (IFH) may occur.…”
Section: Discussionmentioning
confidence: 99%
“…10 Mantle cell lymphoma: conjunctival mass in a female patient Mantle cell lymphoma (MCL) is a rare neoplasm in the ocular adnexa, accounting for 3%-5% of conjunctival B-cell non-Hodgkin lymphomas (NHL). 1,2 Conjunctival MCL typically presents in male patients in the eighth decade and is often advanced at the time of presentation. 3 Treatment typically consists of chemotherapy or radiation, although the prognosis is poor.…”
Section: Discussionmentioning
confidence: 99%